Ultrananocrystalline Diamond Films Deposited in Ar-CO2- CH4 Gas Mixtures by Microwave CVD. Issue 12 (December 2015) - Jie, Feng; Yao, Qi; Jingkai, Sheng; Zhou, Li; Li, Ma; Xianzhe, Wu; Dongping, Hu; Jun, Mei; Zhiming, Yu; Qiuping, Wei
Abstract: Ultrananocrystalline diamond film was deposited by microwave chemical vapor deposition (CVD) system using Ar-CO2 -CH4 as gas source. The effects of process conditions on the morphology of diamond film were investigated. Results show that the compact ultrananocrystalline films with thickness of 5 μm, crystal size of 20 nm and surface roughness below 16 nm can be deposited. The deposition rate is significantly improved by adding CO2 into the Ar-CH4 system. However, the parameter window of gas source for the deposition of compact nanodiamond films is quite narrow when this gas source is employed. Further research is needed to investigate the reasons and optimal process condition.